PERAN KEPALA SEKOLAH DALAM PENGELOLAAN PENDIDIKAN MASA PANDEMI CORONA VIRUS DISEASE (COVID-19) DI SMP NEGERI 2 BANGKO PUSAKO ROKAN HILIR - Jureni Jureni; Zulfan Saam; Daeng Ayub Natuna (STKIP Pesisir Selatan, 2022)
This study aims to: (1) determine the role of school principals in managing teachers during the Corona Virus Disease (Covid-19) pandemic at SMP Negeri 2 Bangko Pusako, Rokan Hilir; (2) knowing the role of school principals in supervising learning during the Corona Virus Disease (Covid-19) pandemic at SMP Negeri 2 Bangko Pusako, Rokan Hilir. (3) knowing the role of the principal in managing parents during the Corona Virus Disease (Covid-19) pandemic at SMP Negeri 2 Bangko Pusako, Rokan Hilir. (4) knowing the role of the principal in leading the school during the Corona Virus Disease (Covid-19) pandemic at SMP Negeri 2 Bangko Pusako, Rokan Hilir. This type of research is descriptive qualitative. Data collection techniques using document review, observation, and interviews. Informants/subjects in this study are elements in schools that can be used as data sources. The type of data obtained is in the form of qualitative descriptive data. The results of this study indicate: (1) Managing teachers is included in the good category. (2) Supervision of Learning has been carried out very well. (3) Managing Parents has been carried out very well. (4) Leading the School has been carried out well. The conclusion that can be drawn is the role of school principals in managing education during the Corona Virus Disease (Covid-19) pandemic. At SMP Negeri 2 Bangko Pusako, Rokan Hilir can already be categorized as good.